COMPARISON OF COST BUDGET ANALYSIS BETWEEN THE 2016 AHSP METHOD, AHSP 2022 METHOD AND THE CONTRACTOR'S CALCULATION METHOD ON THE WARUNG JATI RESTAURANT PROJECT, BEKASI CITY - M. Fanshurullah Asa; M. Rizaldo Julian (DEARSIP : Journal of Architecture and Civil, 2024)
Currently, the culinary business is a form of business that is growing in big cities such as DKI Jakarta and its surrounding cities including Bekasi City, West Java. To build a place of business, it is necessary to calculate an efficient cost budget. Therefore, researchers want to determine the use of economical methods, budget differences, and the causes of differences in cost budget calculations on the Warung Jati Restaurant project, East Bekasi, using the 2016 AHSP, 2022 AHSP and Contractor Calculation methods. In this study, the main problem that makes the difference in the AHSP method is the difference in coefficient values both in labor and materials. Examples of differences in this study are ceramic work, sitting closet work, and site mix concrete work with molen. The results obtained from this study are the 2016 AHSP Method with the Contactor Method by 4.42%, then the difference between the 2022 AHSP and the Contactor Method is 3.92%, and the difference between the 2016 & 2022 AHSP is 0.51%. From the comparison of the cost budget value by following the AHSP standard, the cost budget value is more economical by using the AHSP 2022 method. However, when compared to the Contractor Method, the more economical of the three methods in calculating the cost of the Warung Jati Restaurant project is to use the Contractor Method.